Cytotoxic triterpenoids from the stem barks of Dysoxylum arborescens and Dysoxylum excelsum against MCF-7 breast cancer cell - Achmad Zainuddin,; Sylvia Rachmawati Meilanie,; Darwati,; Kurniawan,; Nurlelasari,; Tati Herlina,; Saputra, Adrian Rizky; Al Anshori, Jamaludin; Tri Mayanti, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Three triterpenoids, taraxerone (1) and 18-epi-taraxerol (2), and masticadienolic acid (3) were isolated for the first time from the stem barks of Dysoxylum arborescens and Dysoxylum excelsum, respectively. Isolation of the compounds was achieved by various extraction and chromatography column techniques, while their chemical structures were elucidated based on spectroscopic data and literature comparison. Compounds 1, 2, and 3 were found to show inhibitory activity against MCF-7 breast cancer cells with IC50 values 792.9, 59.6, and 3.5 µM correspondingly.